A Safe and Innovative Method to Apply Venous Coupler in Oncologic Head and Neck Reconstruction - Naalla, Ravikiran (Indian Journal of Plastic Surgery, 2023)
Venous anastomosis with a coupler device is an effective alternative to the hand-sewn anastomosis technique. Twist in the veins following a coupler anastomosis is a troublesome complication that needs a revision of venous anastomosis. The author proposes a simple technique to reduce the incidence of this complication. This technique is particularly useful in head and neck reconstruction and for beginners in the initial part of the learning curve.
Keywords: venous anastomosis; coupler; twist